PENCEGAHAN PENYALAHGUNAAN OBAT KATEGORI OVER THE COUNTER (OTC) DI DESA SEDARI - Mally Ghinan Sholih; Devi Ratnasari; Marsah R. Utami; M. Januar Ibnu Adham (JURNAL PENGABDIAN MANDIRI, 2023)
Community service has been carried out on Mitigation of Over The Counter (OTC) Drug Abuse Through Education for the Karawang community in Sedari Village, Cibuaya District, Karawang. This activity aims to increase public understanding in the use of drugs and is a joint effort between lecturers and the community in order to create awareness, awareness, understanding and skills of the community in using OTC drugs appropriately and correctly. The Minister of Health of the Republic of Indonesia on November 13, 2015 launched the “Gerakan masyarakat cerdas menggunakan obat” as part of promotive, preventive and community empowerment efforts in increasing rational use of drugs. This community service activity will be carried out through socialization/workshops using lecture, discussion and guidance methods. The results of the service show that the understanding of the Sedari Village community towards getting, using, storing, and properly disposing of OTC drugs increases.